Dog and Bear : three to get ready - Seeger, Laura Vaccaro (New York : Roaring Brook Press, 2009)
Bear has a bucket stuck on his head, but luckily, Dog has a plan. It's not a perfect plan, but in this and two other stories, imperfect plans still work out when good friends help each other.
A Junior Library Guild selection
"A Neal Porter book."
Accelerated Reader/Renaissance Learning
Keywords: Dogs -- Juvenile fiction; Teddy bears -- Juvenile fiction; Friendship -- Juvenile fiction; Dogs -- Fiction; Teddy bears -- Fiction; Friendship -- Fiction